IMPLEMENTATION OF MUDHARABAH PRINCIPLES IN SHARIA LEASING PRODUCTS AND THEIR IMPACT ON ECONOMIC JUSTICE - Siti Nuraini Maksum (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2024)
In the Islamic economic system, one of the increasingly popular financial instruments is Islamic leasing. The principle of mudharabah, which is a form of cooperation between capital owners (mudharib) and capital managers (rabul mal), is used to ensure economic justice between parties involved in sharia leasing transactions. The purpose of this study is to see how the principle of mudharabah is applied in Islamic leasing products and how it impacts economic justice. To achieve this goal, literature, journals, and other relevant sources on the subject are collected through literature study. Studies show that the application of the principle of mudharabah in sharia leasing can benefit economic justice. First, the principle of mudharabah encourages transacting parties to reach an agreement on a fair outcome.